Evaluation of the bridging course offered at a university to foreign students: Batches of 2012 and 2013 - Perez, Beatriz Eugenia Orantes; Mardapi, Djemari (REID (Research and Evaluation in Education), 2015)
This evaluation was a case study of the bridging language program offered at YSU to KNB students, it evaluated the generations 2012/2013. The focus of this evaluation was to evaluate the strengths and weaknesses of the bridging program. This was a summative evaluation used the CIPP method. It was a pragmatic parallel mix-method design research. The analysis technique was descriptive for the qualitative data; and it was descriptive statistical for the quantitative data; Triangulation was used. 15 students, 6 teachers, 10 tutors, 3 administrators were involved. In each component of the evaluation strengths and weaknesses were found. The main strengths were: Clear cultural objectives, experience teachers, tutorials helped students a lot. The main weaknesses were: There is not clear criteria of the level to be reach, tutors lack training and time to prepare, material and assessment needs to be improve, students don't reach an upper intermediate level of the language.